The effects of workplace office ergonomic intervention on work-related posture and musculoskeletal symptoms: a systematic review - Supian, Nor Syafiqah; Munajat, Munayati; Bukry, Saiful Adli (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Office computer workers' sedentary lifestyles and improper posture increase the risk of musculoskeletal symptoms. Previous studies have conducted research regarding the effect of ergonomics on musculoskeletal symptoms, however, there is still some debate on which ergonomic interventions, either a combination of workstation adjustment and educational components or educational components alone give a positive effect on improving the posture and decreasing the musculoskeletal symptoms. Objective: This study was conducted to review the effects of ergonomic interventions; workstation adjustments, and/or educational components on work-related posture and musculoskeletal symptoms among office computer workers. Method: This review analysed articles from ScienceDirect, Taylor & Francis, The Cochrane Library, and PubMed between the year 2003 to 2023. The study screened articles, assessed eligibility using PICOS criteria, and assessed bias risk using RoB2 tools. The data was descriptively analysed. Result: Out of three studies that are included in this systematic review, two studies (one study on the effect of educational components alone; one study on the effect of workstation adjustment with educational components) showed a significant reduction in musculoskeletal symptoms, whilst another study (the effect of workstation adjustment with educational components) showed no significant effect on musculoskeletal symptoms. Besides, only one study (the effect of workstation adjustment with educational components) showed a positive effect on work-related posture. Conclusion: The result showed that there is a positive effect of ergonomic intervention on improving work-related posture and reducing musculoskeletal symptoms, however, it is still inconclusive due to the lack of studies being reviewed.